A hypothesis study on a four-period prevention model for high altitude disease - Xian-Sheng Liu; Xiang-Rong Yang; Lu Liu; Xian-Kui Qin; Yu-Qi Gao (Military Medical Research, 2018)
Abstract Background High altitude disease (HAD) can reduce combat effectiveness and damage the health of soldiers at high altitudes. The objective of this hypothesis study is to build a four-period prevention model for high altitude disease that can be applied at high altitudes of over 3000 m. Presentation of the hypothesis We divided the time at high altitude into nine periods, with three stages from the ascent preparation to the descent to the plain, and applied a continuous dynamic and systematic four-period prevention model across the nine periods. Each period of three stages has its own different measures and targets high altitude health care services for the prevention of high altitude disease. A standard four-period prevention model for high altitude disease was constructed for the high altitude health services at the population level. Testing the hypothesis Our hypothesized HAD prevention model represents a continuous dynamic and systematic four-period prevention model across the nine periods. This hypothesis can be tested from three aspects. The first one isassessment of soldiers' operating efficacies. The second is comparison of the long-term high altitude population health basic data and development and utilization of big data. The third is descent population health status comparative study and historical retrospective study on prevention. Implications As we know, it is necessary to protect soldiers’ health through the ascent and descent. Through the standard four-period model, we can protect soldiers’ health by preventing high altitude diseases, screening the susceptible population, securely tracking their location and maintaining soldiers’ health statuses; we also maintain their operational capabilities, eliminate their psychological fears and ease their family troubles.